Klebsiella in Wildlife: Clonal Dynamics and Antibiotic Resistance Profiles, a Systematic Review - Micaela Quintelas; Vanessa Silva; Sara Araújo; Maria Teresa Tejedor-Junco; José Eduardo Pereira; Gilberto Igrejas; Patricia Poeta (Pathogens)
Klebsiella spp. are a genus of Gram-negative, opportunistic bacteria frequently found in the flora of the mucosal membranes of healthy animals and humans, and in the environment. Species of this group can cause serious infections (meningitis, sepsis, bacteraemia, urinary tract infections, liver damage) and possible death in immunocompromised organisms (and even in immunocompetent ones in the case of hypervirulent K. pneumoniae) that are exposed to them. K. pneumoniae is part of the ESKAPE organisms, and so it is important to understand this genus in terms of multidrug-resistant bacteria and as a carrier of antibiotic resistance mechanisms. As it is a durable bacterium, it survives well even in hostile environments, making it possible to colonize all kinds of habitats, even the mucosal flora of wildlife. This systematic review explores the prevalence of Klebsiella spp. bacteria in wild animals, and the possibility of transmission to humans according to the One Health perspective. The isolates found in this review proved to be resistant to betalactams (blaTEM, blaOXA-48…), aminoglycosides (strAB, aadA2…), fosfomycin, tetracyclines, sulphonamides, trimethoprim, phenicols (catB4), and polymyxins (mcr4).